Description and determinants of the faecal resistome and microbiome of farmers and slaughterhouse workers: A metagenome-wide cross-sectional study. (October 2020) - Van Gompel, Liese; Luiken, Roosmarijn E.C.; Hansen, Rasmus B.; Munk, Patrick; Bouwknegt, Martijn; Heres, Lourens; Greve, Gerdit D.; Scherpenisse, Peter; Jongerius-Gortemaker, Betty G.M.; Tersteeg-Zijderveld, Monique H.G.; García-Cobos, Silvia; Dohmen, Wietske; et al.
Highlights: Food chain workers are exposed to antimicrobial resistant (AMR) bacteria in livestock. We describe faecal resistomes and microbiomes of farmers and slaughterhouse workers. Faecal AMR gene loads in pork exposed workers exceed those in broiler farmers/controls. Resistome and microbiome differences are shown between and within occupational groups. On-farm working hours and working/living on a pig farm determinethe faecal resistome. Contact with livestock may be a determinant for human AMR gene carriage. Abstract: Background: By studying the entire human faecal resistome and associated microbiome, the diversity and abundance of faecal antimicrobial resistance genes (ARGs) can be comprehensively characterized. Prior culture-based studies have shown associations between occupational exposure to livestock and carriage of specific antimicrobial resistant bacteria. Using shotgun metagenomics, the present study investigated 194 faecal resistomes and bacteriomes from humans occupationally exposed to ARGs in livestock (i.e. pig and poultry farmers, employees and family members and pig slaughterhouse workers) and a control population (Lifelines cohort) in the Netherlands. In addition, we sought to identify determinants for the human resistome and bacteriome composition by applying a combination of multivariate (NMDS, PERMANOVA, SIMPER and DESeq2 analysis) and multivariable regression analysis techniques. Results: Pig slaughterhouse workers and pig farmers carried higher total ARG abundances in their stools compared to broiler farmers and control subjects. Tetracycline, β-lactam and macrolide resistance gene clusters dominated the resistome of all studied groups. No significant resistome alpha diversity differences were found among the four populations. However, the resistome beta diversity showed a separation of the mean resistome composition of pig and pork exposed workers from broiler farmers and controls, independent of their antimicrobial use. We demonstrated differences in resistome composition between slaughter line positions, pig versus poultry exposed workers, as well as differences between farmers and employees versus family members. In addition, we found a significant correlation between the bacteriome and resistome, and significant differences in the bacteriome composition between and within the studied subpopulations. Finally, an in-depth analysis of pig and poultry farms – of which also farm livestock resistomes were analysed – showed positive associations between the number of on-farm working hours and human faecal AMR loads. Conclusion: We found that the total normalized faecal ARG carriage was larger in persons working in the Dutch pork production chain compared to poultry farmers and controls. Additionally, we showed significant differences in resistome and bacteriome composition of pig and pork exposed workers compared to a control group, as well as within-population (farms, slaughterhouse) compositional differences. The number of on-farm working hours and the farm type (pig or broiler) that persons live or work on are determinants for the human faecal resistome. Overall, our results may suggest direct or indirect livestock contact as a determinant for human ARG carriage. Future studies should further focus on the connection between the human and livestock resistome (i.e. transmission routes) to substantiate the evidence for livestock-associated resistome acquisition.